Quality Analysis of Outbound Container Stuffing using the Six Sigma Method in a Logistic Shipping Company in Surabaya - Devina Puspita Sari; Darien Morieno; Alfred Bawole (Surabaya State Polytechnic of Shipbuilding, 2024)
In the current era of globalization, the role of trade as a driver of a country's economic growth is increasingly significant (Hasoloan, 2013). Good logistics movement is the key to equitable economic development. This study aims to analyze the quality of container stuffing outbound flows in a logistics shipping company in Surabaya using the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) method. The main problem identified was operational delays due to the scarcity of empty containers at container yards, which occurred 130 times in the 4th quarter of 2023. The analysis using the Six Sigma method showed a DPMO value of 477,900 and a sigma value of 1.56, which indicated an inefficiency in operations. The DMAIC approach proposes improvement solutions to increase container availability and optimize trucking operations, thereby increasing On-Time Performance (OTP) from 88% to 90%. Implementing these improvements is expected to increase productivity and customer satisfaction and reduce operational costs due to delays.